Association between hepatitis B virus infection and colorectal liver metastasis: a meta-analysis. Issue 1 (1st January 2021) - Liu, Rongqiang; Kong, Weihao; Deng, Mingbin; Lin, Guozhen; Dai, Tianxing; Ye, Linsen
ABSTRACT: The paper aims to assess the association between Hepatitis B Virus infection and colorectal liver metastasis by conducting a meta-analysis. The relevant studies were searched until 24 July 2020, Studies that assessed the correlation between HBV infection and CRLM were recruited. A random effects model was applied to calculate the odds ratio (OR) with 95% confidence interval (CI). All data analyses were performed by STATA 12.0 software. Ten studies involving 17529 participants were included in the study. The results shown that there was obvious association between HBV infection and CRLM (OR: 0.51, 95% CI: 0.28–0.91). The study type and case–control rate may be the main causes of heterogeneity. In addition, HBV infection had no association with extrahepatic metastasis or prognosis of patients with CRLM. Sensitivity analyses confirmed that the results were stable, and Egg's test indicated that there was no publication bias. Patients with HBV infection have the reduced risk of CRLM. GRAPHICAL ABSTRACT: uf0001